2007
DOI: 10.1177/1352458506071170
|View full text |Cite
|
Sign up to set email alerts
|

Coping and quality of life in one hundred and thirty five subjects with multiple sclerosis

Abstract: Our study clearly demonstrated that psychological and social well-being were substantially affected by the disease course. These results encourage us to develop interventions focused on coping strategies and which are better adapted to individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
4
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 53 publications
7
77
4
3
Order By: Relevance
“…Depression, anxiety and mood disorders have been reported as important factors that affect disease progression. Supporting our findings, there are some reports showing higher rates of depression and anxiety together with more profound loss of emotional control in patients with secondary-progressive MS 10 . Our study also demonstrated higher total POMS scores in women compared to men, indicating more profound effects on mood state and mood characteristics such as depression-dejection, and fatigue-inertia.…”
Section: Discussionsupporting
confidence: 91%
“…Depression, anxiety and mood disorders have been reported as important factors that affect disease progression. Supporting our findings, there are some reports showing higher rates of depression and anxiety together with more profound loss of emotional control in patients with secondary-progressive MS 10 . Our study also demonstrated higher total POMS scores in women compared to men, indicating more profound effects on mood state and mood characteristics such as depression-dejection, and fatigue-inertia.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, most patients (53%) adopted a task-oriented coping strategy. Yet, many studies report the emotion-oriented coping strategy as the preferred one in MS patients [15,16,17]. This difference may be due to the definition of emotion-oriented coping strategy that may or may not include avoidance-oriented strategy, or may reflect a study enrolment bias as patients with current severe depression or suicidal ideations were excluded because of treatment contraindications.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive types of MS demand more frequent adjustments to more severe challenges compared to RRMS (Gaudino, Chiaravalloti, DeLuca, & Diamond, 2001;Heaton, Nelson, Thompson, Burks, & Franklin, 1985) and there is some evidence that people with SPMS show increased distress compared to those with RR and PPMS (Montel & Bungener, 2007;Vleugels et al, 1998). Despite the particular challenges of…”
Section: Running Head: Adjustment In Progressive Msmentioning
confidence: 99%